Fetuin-A in association with metabolic syndrome and its components - Singh, Manisha; Sreenivasulu, Karli; Choudhary, Sarita (International Journal of Research in Medical Sciences, 2021)
Background: Fetuin-A also known as α-2-Heremans-Schmid glycoprotein, is a multifunctional plasma glycoprotein. In developing countries like India, the metabolic syndrome (MetS) is on an exponential rise. The factors that characterize MetS are also associated with the atherosclerotic process, in which an important role is played by serum fetuin-A levels. The aim of present study is an assessment of serum fetuin-A level and its association with other components of MetS in age matched healthy controls and MetS subjects. Methods: Total eighty (N=80) subjects (40 MetS cases and 40 age and gender matched controls) were included based on inclusion and exclusion criteria. The fasting venous samples were collected to measure the fasting glucose, lipid profile, glycated hemoglobin, insulin and fetuin-A levels. The serum fetuin levels were estimated by ELISA kit. Results: The serum fetuin-A levels were significantly higher in MetS cases as compared to the control group (p value<0.001). Other components like insulin, HbA1c and HOMA-IR levels were raised in MetS compared to controls. In correlation analysis the serum fetuin-A levels were positively correlated with fasting insulin levels (r=0.36, p=0.02), fasting glucose (r=0.39, p=0.01) and triglycerides (r=0.34, p=0.03). Also, in receiver operating characteristic curve analysis the AUC for fetuin-A is 0.76 (95% CI: 0.65-0.86) was observed. Conclusions: We found that serum fetuin-A levels were strongly and independently associated with MetS. Our finding suggests that fetuin-A could be a useful marker in clinical practice in the future for the early diagnosis of MetS.